Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004375.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Catheter policies for management of long term voiding problems in adults with neurogenic bladder disorders

Abstract: Despite a comprehensive search no evidence from randomised or quasi-randomised controlled trials was found. It was not possible to draw any conclusions regarding the use of different types of catheter in managing the neurogenic bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 7 publications
0
40
0
1
Order By: Relevance
“…In a 38-month prospective observational study involving 128 patients with acute spinal cord injuries, the incidence rates per 100 person-days for CA-bacteriuria and CA-UTI, respectively, were 5 and 2.72 cases for men with indwelling urethral catheters (128 patients), 2.95 and 0.41 cases for men with clean intermittent catheterization (124 patients), 2.41 and 0.36 cases for men with condom catheters (41 patients), and 0.96 and 0.34 cases for women with suprapubic catheterization (10 patients), respectively [25]. Although there are no randomized, controlled trials that have compared long-term catheterization methods (intermittent urethral catheterization, indwelling urethral or suprapubic catheterization, and external catheter for men) in managing voiding problems in patients with [159] or without neurogenic bladders, clean intermittent catheterization has become the standard of care for appropriate women and men with spinal cord injuries [16]. In addition, clean intermittent catheterization is a more commonly used alternative in men with bladder atonia and elderly patients who need assistance with voiding [21,77,160].…”
Section: Evidence Summarymentioning
confidence: 99%
“…In a 38-month prospective observational study involving 128 patients with acute spinal cord injuries, the incidence rates per 100 person-days for CA-bacteriuria and CA-UTI, respectively, were 5 and 2.72 cases for men with indwelling urethral catheters (128 patients), 2.95 and 0.41 cases for men with clean intermittent catheterization (124 patients), 2.41 and 0.36 cases for men with condom catheters (41 patients), and 0.96 and 0.34 cases for women with suprapubic catheterization (10 patients), respectively [25]. Although there are no randomized, controlled trials that have compared long-term catheterization methods (intermittent urethral catheterization, indwelling urethral or suprapubic catheterization, and external catheter for men) in managing voiding problems in patients with [159] or without neurogenic bladders, clean intermittent catheterization has become the standard of care for appropriate women and men with spinal cord injuries [16]. In addition, clean intermittent catheterization is a more commonly used alternative in men with bladder atonia and elderly patients who need assistance with voiding [21,77,160].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Two Cochrane systematic reviews confirmed a lack of randomized controlled data [37,38]. Recent studies, however, provided some promising results.…”
Section: Catheter Typementioning
confidence: 99%
“…Infobox 1; [18]). Das liegt sicher weniger an der fehlenden Evidenz der Unterschiede zwischen verschiedenen therapeutischen Optionen als am Fehlen evidenzbasierter Daten [45].…”
Section: Dauerkatheterismusunclassified